Peningkatan Keterampilan Menggiring Bola Melalui Metode Latihan Kelincahan Pada Siswa Pelajar Kabupaten Gowa - Muslim Bin Ilyas; Alimin hamzah; Muh. Ilham Aksir (Journal Physical Health Recreation (JPHR), 2024)
The problem formulation in this research is improving ball dribbling skills through agility training methods for Gowa district students. Meanwhile, the aim of this research is to find out whether there is an increase in dribbling skills through agility training methods among Gowa district students. The type of research that will be used in this research is quantitative descriptive analysis. In this research design, research subjects were selected using purposive sampling based on certain characteristics, research so that the research subjects are homogeneous. Meanwhile, data analysis uses SPSS 21 using descriptive tests, normality tests and hypothesis tests. Based on the results of the analysis, the results of the data processing tests show that there has been an increase in dribbling skills through agility training methods in Gowa district students. has variable data. Improved ball dribbling skills through agility training methods for Gowa district students. This can be seen from the SPSS test results, namely from the regression test data from the regression test data before training. N (sample) 20 people, Mean 19.2965, T table value 60.676 and sig value (2 tailed) 0.00 (p<0.05). means that the data before training is normally distributed. From the regression test data after training N (sample) 20 people, the mean is 1.1325, the T table value is 74.538 and the sig value (2 tailed) is 0.00 (p<0.05). This means that the data after training is normally distributed and from this data it can be seen that there is an increase in dribbling skills through the agility training method among Gowa district students with a difference of 1.1325.